National contributions to climate change mitigation from agriculture: allocating a global target - Wollenberg, Eva Karoline; Richards, Meryl B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Presentation by Lini Wollenberg on behalf of Meryl Richards, both from CCAFS and the University of Vermont Gund Institute for Environment International conference on agricultural emissions and food security: Connecting research to policy and practice 10-13 September 2018 Berlin, Germany